Mechanoradicals in tensed tendon collagen as a source of oxidative stress - Zapp, Christopher; Obarska-Kosinska, Agnieszka; Rennekamp, Benedikt; Kurth, Markus; Hudson, David M.; Mercadante, Davide; Barayeu, Uladzimir; Dick, Tobias P.; Denysenkov, Vasyl; Prisner, Thomas; Bennati, Marina; Daday, Csaba; et al. (Nature Communications, 2020)
As established nearly a century ago, mechanoradicals originate from homolytic bond scission in polymers. The existence, nature and biological relevance of mechanoradicals in proteins, instead, are unknown. We here show that mechanical stress on collagen produces radicals and subsequently reactive oxygen species, essential biological signaling molecules. Electron-paramagnetic resonance (EPR) spectroscopy of stretched rat tail tendon, atomistic molecular dynamics simulations and quantum-chemical calculations show that the radicals form by bond scission in the direct vicinity of crosslinks in collagen. Radicals migrate to adjacent clusters of aromatic residues and stabilize on oxidized tyrosyl radicals, giving rise to a distinct EPR spectrum consistent with a stable dihydroxyphenylalanine (DOPA) radical. The protein mechanoradicals, as a yet undiscovered source of oxidative stress, finally convert into hydrogen peroxide. Our study suggests collagen I to have evolved as a radical sponge against mechano-oxidative damage and proposes a mechanism for exercise-induced oxidative stress and redox-mediated pathophysiological processes.